Characterization Of Bioplastic from Cellulose Acetate Empty Bunches Oil Palm and Canna Bulb Flour (Canna edulis Ker) With Addition of Variations of Glycerol - Musthofa Lutfi; Gunomo Djoyowasito; Bambang Dwi Argo; Lita Puspita Rizka Perdana (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2025)
Bioplastics are environmentally friendly materials that serve as alternatives to synthetic plastics, capable of being decomposed by microorganisms. Starch, commonly sourced from tubers such as canna tubers, is one of the primary natural components used in bioplastic production. This study utilized a completely randomized factorial design with glycerol as a plasticizer and cellulose acetate from Oil Palm Empty Fruit Bunches (OPEFB) as a reinforcement agent. Glycerol was varied at concentrations of 1, 2, 3, 4, and 5 ml, while cellulose acetate OPEFB was varied at 1, 1.5, 2, 2.5, and 3 g. The resulting bioplastics underwent mechanical testing, including tensile strength, elongation, elasticity, water absorption, solubility, and biodegradability. The highest tensile strength (20.56 MPa) was observed with 2 ml glycerol and 1.5 g cellulose acetate OPEFB. The best elongation (33.33%) occurred with 4 ml glycerol and 1 g cellulose acetate OPEFB. Maximum elasticity (2.86 MPa) was achieved with 2 ml glycerol and 2.5 g cellulose acetate OPEFB. Optimal water absorption (12.54%) was recorded with 1 ml glycerol and 1 g cellulose acetate OPEFB, while the highest solubility (43.97%) was observed with 5 ml glycerol and 3 g cellulose acetate OPEFB. The greatest biodegradability (88.75%) was achieved with 5 ml glycerol and 1.5 g cellulose acetate OPEFB. These findings highlight the potential of starch-based bioplastics reinforced with cellulose acetate OPEFB to achieve desirable mechanical and environmental performance characteristics.